2019
DOI: 10.1038/s41467-019-12304-4
|View full text |Cite
|
Sign up to set email alerts
|

DNA mechanotechnology reveals that integrin receptors apply pN forces in podosomes on fluid substrates

Abstract: Podosomes are ubiquitous cellular structures important to diverse processes including cell invasion, migration, bone resorption, and immune surveillance. Structurally, podosomes consist of a protrusive actin core surrounded by adhesion proteins. Although podosome protrusion forces have been quantified, the magnitude, spatial distribution, and orientation of the opposing tensile forces remain poorly characterized. Here we use DNA nanotechnology to create probes that measure and manipulate podosome tensile force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(101 citation statements)
references
References 82 publications
8
92
0
Order By: Relevance
“…[52] Recent work by Glazier et al showed that integrins residing in the podosomal ring surrounding its actin core apply tensile forces on RGD ligands needed for podosome stability and maturation. [53] However, these tensile forces are controlled by the polymerization of the actin core but not by actomyosin contractions in the podosomal ring [53] and seem to be the result of local forces needed to stabilize actin protrusion into the ECM. Indeed, the integrity of the podosomal ring is needed to support actin polymerization and protrusion at the core, as depletion of talin and vinculin decreases protrusion force.…”
Section: Mechanosensory Function Of Podosomes/invadopodiamentioning
confidence: 99%
“…[52] Recent work by Glazier et al showed that integrins residing in the podosomal ring surrounding its actin core apply tensile forces on RGD ligands needed for podosome stability and maturation. [53] However, these tensile forces are controlled by the polymerization of the actin core but not by actomyosin contractions in the podosomal ring [53] and seem to be the result of local forces needed to stabilize actin protrusion into the ECM. Indeed, the integrity of the podosomal ring is needed to support actin polymerization and protrusion at the core, as depletion of talin and vinculin decreases protrusion force.…”
Section: Mechanosensory Function Of Podosomes/invadopodiamentioning
confidence: 99%
“…Cellsubstrate interactions are also highly relevant to assess mechanotransduction and techniques such as traction force microscopy and magnetic tweezers can be applied to survey such interactions. Forces in the order of pico-Newtons, applied by integrins on ligands, have also been assessed by DNA mechanotechnology (Brockman et al, 2018;Glazier et al, 2019;. However, significant challenges regarding the integrity of the DNA probes in cell culture conditions and the type of receptor-ligand interactions that can be probed remain (Ma and Salaita, 2019;Yasunaga et al, 2019).…”
Section: Conclusion and Outlooksmentioning
confidence: 99%
“…The second demonstration of mechanical proofreading highlighted the role of forces in podosome formation. In this context, actin-pushing forces generated in podosomes depend on specific picoNewton-scale pulling forces that are applied by integrin receptors in the ring complex (Glazier et al, 2019).…”
Section: Physics Of the Cellmentioning
confidence: 99%